Prebiotics and probiotics for depression and anxiety: A systematic review and meta-analysis of controlled clinical trials - Liu, Richard T.; Walsh, Rachel F.L.; Sheehan, Ana E. (Neuroscience and biobehavioral reviews, 2019)
•A meta-analysis of prebiotic and probiotic trials for depression and anxiety.•Prebiotics did not differ from placebo for depression or anxiety.•Probiotics yielded small but significant effects for depression and anxiety.•Probiotic effects were larger for clinical than community samples for depression.•More studies of clinical samples are needed fully to evaluate therapeutic potential. With growing interest in the gut microbiome, prebiotics and probiotics have received considerable attention as potential treatments for depression and anxiety. We conducted a random-effects meta-analysis of 34 controlled clinical trials evaluating the effects of prebiotics and probiotics on depression and anxiety. Prebiotics did not differ from placebo for depression (d = −.08, p = .51) or anxiety (d = .12, p = .11). Probiotics yielded small but significant effects for depression (d = −.24, p < .01) and anxiety (d = −.10, p = .03). Sample type was a moderator for probiotics and depression, with a larger effect observed for clinical/medical samples (d = −.45, p < .001) than community ones. This effect increased to medium-to-large in a preliminary analysis restricted to psychiatric samples (d = −.73, p < .001). There is general support for antidepressant and anxiolytic effects of probiotics, but the pooled effects were reduced by the paucity of trials with clinical samples. Additional randomized clinical trials with psychiatric samples are necessary fully to evaluate their therapeutic potential.